DAMPAK CUACA ANTARRIKSA PADA VARIABILITAS IKLIM DI INDONESIA - Wilson Sinambela; Iyus E.Rusnadi; Nana Suryana (Lembaga Penerbangan dan Antariksa Nasional, 2006)
Since a long time ago the Sun as the main source of energy of the Earth is considered to give influence the Earth's climate. It is seen from the analysis of solar activity influence on surface air temparature in various cities in Indonesian area using available data. The result Weighted Wavelet Z-transform (WWZ) analysis of surface air temperature which shows siilarity between periodicity of that of solar activity, especially about 11 yaer, is the first indications of the influence of space weather to the Indonesian climate variability. Additionally, from statistical analyzes by using 11 years-running moving averages, it is seen that the pattern of surface air temperature changes follows the pattern of solar activity variability, although they are sometimes out of phase and move ahead in about 5-15 years. Furthermore, although time series data of surface air temperature is limited, the result shows a good correction between the changes of surface air temperature and solar cycle length/SCL with an applied smoothing with the coefficients 1-2-2-2-1 (from now on we call SCL 12221). We therefore find that this agreement supports (although it does not prove) the sugestion of a direct solar activity influence on surface air temperature in Indonesia.